2021
DOI: 10.1088/1361-6528/abf8da
|View full text |Cite
|
Sign up to set email alerts
|

Controllable morphology of electrospun nanofiber membranes with tunable groove structure and the enhanced filtration performance for ultrafine particulates

Abstract: As researchers are striving to develop high-performance filtration membranes with hierarchical micro/nano structures, the challenges and costs of processing often limit creative innovation. Here, we propose a polyethersulfone/polyacrylonitrile (PES/PAN) nanofiber membrane with groove structure by electrospinning and facile post-processing. The resulted membrane can form a groove structure on the surface of the fiber after being soaked in chloroform, thereby increasing the collision probability and extending th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 43 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…Efforts have also been made to improve the ltration efficiency of masks by reducing the diameter of lter bers, increasing the affinity between particles and lter fabrics, optimizing the ber structure to form groove structures on the surface to trap more ultrane particles, etc. [111][112][113][114] The degree of t between the mask and wearer also affects the ltration and protection performance of the mask since it was indicated that the gaps between the mask and wearer could lead to over 60% decline of ltration efficiency. 10 Notably, 3D printing technology could act as a replenishment in the early shortage of masks and help to customize individual-tting face seal masks and respirators.…”
Section: Improvement Of Mask Performancementioning
confidence: 99%
“…Efforts have also been made to improve the ltration efficiency of masks by reducing the diameter of lter bers, increasing the affinity between particles and lter fabrics, optimizing the ber structure to form groove structures on the surface to trap more ultrane particles, etc. [111][112][113][114] The degree of t between the mask and wearer also affects the ltration and protection performance of the mask since it was indicated that the gaps between the mask and wearer could lead to over 60% decline of ltration efficiency. 10 Notably, 3D printing technology could act as a replenishment in the early shortage of masks and help to customize individual-tting face seal masks and respirators.…”
Section: Improvement Of Mask Performancementioning
confidence: 99%
“…It is preferable to have high values for specific surface area, pore volume, size tunability, and permeability. It is a perfect candidate for membrane-based water purification filters [ 8 ]. Various nanocomposite nanofibrous membranes and nanomaterials were used in their fabrication to improve the structural and functional properties.…”
Section: Introductionmentioning
confidence: 99%
“…10 The development of micro and nano technology has brought great prospects to the field of air filtration, and micro-nano fiber nonwovens exhibit the characteristics of high porosity, high specific surface area, high surface energy and activity, high fiber fineness, and homogeneity, which make them excellent air filter materials. [11][12][13][14][15][16] With the development of electrospinning technology, electrospun micronano fiber materials have been extensively used in the field of air filtration. Patanaik et al, 17 who prepared a three-layer composite fiber filter material with a middle layer of polyethylene oxide (PEO) nanofiber and upper and lower layers of nonwoven fabrics, found that the filtration efficiency increases with the increase of the diameter of PEO nanofibers.…”
Section: Introductionmentioning
confidence: 99%